Differences in responses of invasive and native plants to climate change: a case study of Bidens (Asteracea) from China - Xiao, Haiyan; Liao, Da; Zhang, Shujian; Zhang, Yuxin; Rehab, Omer Elnour; Zeng, Jianjun; Yan, Xiaohong; Su, Qitao; Zhou, Bing (Frontiers in Plant Science, 2025)
Global warming has emerged as one of the most pressing environmental challenges. Concurrently, plant invasion has been exacerbated by ongoing climate change, posing a severe ecological threat. This study investigates the distribution patterns of both invasive and native species within the Bidens genus and their responses to projected climate change. The MaxEnt model, was used to predict the potential distribution ranges under both current and future climate conditions. The results showed a distinct difference in suitable area distributions between invasive and native species. Under future climate scenarios, most studied species (except B. pilosa, B. maximowicziana, and B. radiata) showed an expansion in their suitable habitats. Notably, we observed a latitudinal migration pattern in Bidens species distribution, with invasive species primarily influenced by precipitation during the warmest quarter, while native species were more affected by anthropogenic factors. These results underscore the need for enhanced public awareness of invasion risks and the establishment of dedicated protection zones for both invasive and native species. This study provides critical insights into the potential distribution patterns of Bidens species under climate change. It also, offers valuable scientific support for development of invasive species management strategies and native species conservation mechanisms.